Bio-management of postharvest diseases and mycotoxigenic fungi - Sharma, Neeta, Dr.; Bhandari, Avantina S. (Boca Raton, FL : CRC Press, 2021)
"There is an ever-increasing demand for more food but one of the stumbling blocks to achieving this goal is quality and quantity losses due to various pests and pathogens and the mycotoxins synthesized by these harmful biotic entities. Thus far, strategies employed to manage these post-harvest diseases and mycotoxins decontamination include established physical, cultural, and chemical methods. Recently, the application of chemicals to reduce decay and deterioration caused by various pathogens has been impeded as these hazardous chemicals contaminate the environment, enter the food chain, and destroy beneficial microorganisms and pests by aiming at non-target microorganisms. In light of this, the usage of eco-friendly and non-polluting alternatives to chemical pesticides is the call of the hour. Bio-management of Postharvest Diseases and Mycotoxigenic Fungi deals with the current state and future prospects of using various bio-management techniques that are natural, eco-friendly, and environmentally safe. It aims to increase awareness of their potential as well as sensitizing readers to the various aspects of biologicals in pest control. This book disseminates notable and diversified scientific work carried out by leading experts in their own field. Written by qualified scientists in each of their respective disciplines, it can serve as a current and comprehensive treatise on the emerging field of bio-management of postharvest diseases and mycotoxin decontamination by products that are "generally regarded as safe.""--
Postharvest Biological Control -- Antagonists, Microbiomes, and Beyond -- Managing Post harvest Diseases- Classical vs New Technologies -- Chitosan: an antimicrobial coating to reduce pre and postharvest diseases of fruits and vegetables -- Biobased Coatings: An alternative approach in managing post-harvest diseases -- Non-chemical management of postharvest diseases of mango -- Ecofriendly combating natural essential oils against post harvest phytopathogenic fungi: Holistic overview -- Entomopathogenic Biopesticides: Opportunities and Challenges -- Bioactive Plant Metabolites as Stored Product Protectants -- Mycotoxins, Mycotoxicosis and Managing Mycotoxin Contamination: A Review -- Bio-decontamination of Mycotoxin Patulin -- Decontamination of Mycotoxigenic fungi by Phytochemicals -- Prevention and Control Strategies of Aflatoxin Contamination -- Nano Magic Bullets: an ecofriendly approach to manage plant diseases. -- CAP -- a novel approach to manage fungal spoilage and mycotoxin decontamination.
OCLC-licensed vendor bibliographic record.
Keywords: Food crops -- Diseases and pests -- Biological control; Mycotoxins; Toxigenic fungi; Biological decontamination; TECHNOLOGY / Agriculture / General; TECHNOLOGY / Food Science